2008
DOI: 10.1111/j.1467-7679.2008.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Preferences for Agri‐environmental Change at the Bhoj Wetland, India

Abstract: Incentive-based approaches have gained policy interest in linking change in agricultural land management with environmental conservation. This article investigates how scheme design influences smallholder farmers' decisions to switch to organic farming to reduce water pollution, drawing on a study at a Ramsar wetland site providing water for the city of Bhopal. Results from a choice experiment suggest that transitional payments are necessary to overcome farmer constraints to adopt organic farming, and that eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Communal management can have mixed results on farmers' WTA. Studies such as Hope et al (2008) and reported a positive correlation to farmers' preferences. Hope et al (2008) reported that farmers prefer working as a group rather than as individuals.…”
Section: Prescription Attributesmentioning
confidence: 96%
See 1 more Smart Citation
“…Communal management can have mixed results on farmers' WTA. Studies such as Hope et al (2008) and reported a positive correlation to farmers' preferences. Hope et al (2008) reported that farmers prefer working as a group rather than as individuals.…”
Section: Prescription Attributesmentioning
confidence: 96%
“…Studies such as Hope et al (2008) and reported a positive correlation to farmers' preferences. Hope et al (2008) reported that farmers prefer working as a group rather than as individuals. reported that older farmers (> 60 years) show a higher willingness for collective participation than younger farmers in olive groves of plain areas.…”
Section: Prescription Attributesmentioning
confidence: 96%
“…Experimental choice modelling originates from market research, but is increasingly used in environmental, agricultural and development economics, in, for example, the analysis of the effect of food labelling on consumer behaviour (Loureiro and Umberger, 2007;Rousseau and Vranken, 2013), environmental conservation (Hope et al, 2008;De Valck et al, 2014), and agricultural technology adoption (Ward et al, 2014;Lambrecht et al, 2015). Choice experiments have previously been used to assess contract preferences in developing countries, specifically to assess farmers' preferences for production and marketing contracts in Vietnam and Ethiopia (Schipmann and Qaim, 2011;Abebe et al, 2013), and for labour contracts of health workers in rural areas (Mandeville et al, 2014).…”
Section: Choice Experiments Designmentioning
confidence: 99%
“…Many of these studies applied choice experiment (CE) technique to analyze farmers’ preferences for specific characteristics (attributes) of the investigated issue, as for the agri-environmental subsidy schemes’ features. Contrary to this, to date the academic literature on farmers’ preferences for key design attributes of an EC scheme for agricultural products is rare, with the exception of few examples in developing countries (Hope et al, 2008; Ibnu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%